2005
DOI: 10.1111/j.1075-122x.2005.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocutaneous Nocardiosis in a Lymphopenic Breast Cancer Patient under Treatment with Docetaxel

Abstract: A 65-year-old woman with metastatic breast cancer received 10 courses of chemotherapy with docetaxel 100 mg/m 2 and achieved considerable symptomatic relief despite minimal disease regression. Before her last course, a pustule appeared over her right ankle, which was aspirated for smear and culture. Profound lymphopenia (lymphocytes 100/ µ l) with normal granulocyte counts were also noticed in her peripheral blood. Despite 4 days of empirical treatment with amoxicillin and clavulanate, the lesion ulcerated ( F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Seven out of the 10 patients had pulmonary diseases including pulmonary lesions induced by underlying rheumatic diseases, a history of pulmonary tuberculosis, and pulmonary aspergillosis (Table 2). In contrast to the previous reports suggesting the association between Nocardia infection and lymphocytopenia [13, 14], white blood cell (WBC) counts and lymphocyte counts in peripheral blood in our patients were within normal limits (Table 2). In addition, no patients had severe hypogammaglobulinemia or hypoalbuminemia.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Seven out of the 10 patients had pulmonary diseases including pulmonary lesions induced by underlying rheumatic diseases, a history of pulmonary tuberculosis, and pulmonary aspergillosis (Table 2). In contrast to the previous reports suggesting the association between Nocardia infection and lymphocytopenia [13, 14], white blood cell (WBC) counts and lymphocyte counts in peripheral blood in our patients were within normal limits (Table 2). In addition, no patients had severe hypogammaglobulinemia or hypoalbuminemia.…”
Section: Resultscontrasting
confidence: 99%
“…On the other hand, lymphocytopenia and CMV infection, which have been suggested to be associated with Nocardia infection in patients with organ transplantation or neoplastic diseases [6, 13, 14], were not identified in our patients with rheumatic diseases who developed Nocardia infection (Table 2) possibly due to the relatively low incidence of lymphocytopenia and CMV infection in these conditions [18, 19]. Taken together, these results suggest that the risk factors for development of Nocardia infection can be different in patients with rheumatic diseases compared to those with organ transplantation or neoplastic diseases presumably because of the differences in the preexisting immunological abnormalities and/or the therapy for underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The possible relationship between Nocardia infection and lymphocytopenia had been observed in previous studies. 2 , 4 5 , 31 32 In AIDS patients, it was reported that the incidence of nocardiosis was ∼140-fold higher than that in the general population, and those whose peripheral CD4 + T-cell counts were < 0.1 × 10 9 /l were at the highest risk. 2 , 4 5 Because more than half of our cases had lower CD4 + T-cell counts, it appeared that lymphocytopenia, particularly low peripheral CD4 + T-cell counts, may be a risk factor in patients with autoimmune disease complicated by pulmonary nocardiosis.…”
Section: Discussionmentioning
confidence: 99%